Physical activity and risk of breast cancer in premenopausal women - Colditz, G A (Nature Publishing Group, 2003)
Physical activity appears to be inversely related to risk of breast cancer, yet the results remain inconsistent. To evaluate this relation among premenopausal women and examine variation in risk according to level of obesity and use of oral contraceptives (OCs), the authors examined data from the Nurses’ Health Study II. During 10 years of follow-up, 849 cases of invasive premenopausal breast cancer were confirmed. Physical activity was assessed by self-report at baseline and during follow-up using a validated questionnaire. Total physical activity was unrelated to risk of breast cancer. Women engaging in ⩾27 metabolic equivalent (MET)-h week(−1) had a multivariate-adjusted relative risk (RR) of 1.04 (95% confidence interval (CI) 0.82–1.33) compared to those in the <3 MET-h week(−1) category. Among women with a BMI ⩾30 kg m(−2), we observed a significant positive dose–response relation (P=0.04). Activity was unrelated to breast cancer risk at lower levels of BMI. A test for interaction between activity and BMI (<30, ⩾30 kg m(−2)) was statistically significant (P=0.02). Among current OC users, higher activity was associated with a non-significantly lower risk of breast cancer (RR=0.59, 95% CI 0.30–1.16 for ⩾27 vs <9 MET-h week(−1), P for linear trend=0.14). These results show no overall association between physical activity and risk of breast cancer among premenopausal women, but suggest that the effect of physical activity could be substantially modified by the underlying degree of adiposity. The potential interactions between physical activity, adiposity, and current use of OCs require further study.